Sosialisasi Pada PT. Empat Enam Jaya Gudang Penyimpanan Ammonium Nitrat Di KM 24 Karang Joang Balikpapan - Hadiyono, Hadiyono; Purwanti , Sri; Saputra, Dharma; luqmantoro, luqmantoro (EUNOIA, 2023)
Empat Six Jaya, located at km 24 Karang Joang, Balikpapan, is a company engaged in services for temporary storage of ammonium nitrate. The potential for fires to occur in warehouses or storage areas for materials in open and closed spaces can result in losses and the consequences of fire incidents. in the workplace can result in loss of life, material losses, loss of employment and other losses. The method used to achieve the goal is the method of discussion and practice (learning by doing).